Erratum: Endovascular Management of a Major Vascular Complication after Orthognatic Surgery - Benndorf, G. (Interv Neuroradiol, 1999)
We describe the effective endovascular management of a severe haemorrhagic complication in a 24 year old man which could not be controlled by surgical means. Major bleeding caused by bilateral injured internal maxillary arteries after orthognatic surgery occurred. Angiography proved to be efficient in exactly localizing the bleeding sites while endovascular occlusion ultimately stopped the bleeding in a life-threatening situation for the patient.